Mycobacteria-Specific T Cells May Be Expanded From Healthy Donors and Are Near Absent in Primary Immunodeficiency Disorders - Patel, Shabnum; Lang, Haili; Sani, Gelina; Freeman, Alexandra F.; Leiding, Jennifer; Hanley, Patrick J.; Cruz, Conrad Russell; Grant, Melanie; Wang, Yunfei; Oshrine, Benjamin; Palmer, Cindy; Holland, Steven M.; et al. (Frontiers in Immunology, 2019)
Mycobacterial Infections can be severe in patients with T-cell deficiency or phagocyte disorders, and treatment is frequently complicated by antimicrobial resistance. Restoration of T-cell immunity via stem cell transplantation facilitates control of mycobacterial infections, but presence of active infections during transplantation is associated with a higher risk of mortality. Adoptive T cell immunotherapy has been successful in targeting viruses, but has not been attempted to treat mycobacterial infections. We sought to expand and characterize mycobacterial-specific T-cells derived from healthy donors in order to determine suitability for adoptive immunotherapy. Mycobacteria-specific T-cells (MSTs) were generated from 10 healthy donors using a rapid ex vivo expansion protocol targeting five known mycobacterial target proteins (AG85B, PPE68, ESXA, ESXB, and ADK). MSTs were compared to T-cells expanded from the same donors using lysate from M. tuberculosis or purified protein derivative from M. avium (sensitin). MST expansion from seven patients with primary immunodeficiency disorders (PID) and two patients with IFN-γ autoantibodies and invasive M. avium infections. MSTs expanded from healthy donors recognized a median of 3 of 5 antigens, with production of IFN-γ, TNF, and GM-CSF in CD4+ T cells. Comparison of donors who received BCG vaccine (n = 6) to those who did not (n = 4) showed differential responses to PPE68 (p = 0.028) and ADK (p = 0.015) by IFN-γ ELISpot. MSTs expanded from lysate or sensitin also recognized multiple mycobacterial antigens, with a statistically significant differences noted only in the response to PPE68 (p = 0.016). MSTs expanded from patients with primary immunodeficiency (PID) and invasive mycobacterial infections showed activity against mycobacterial antigens in only two of seven subjects, whereas both patients with IFN-γ autoantibodies recognized mycobacterial antigens. Thus, MSTs can be generated from donors using a rapid expansion protocol regardless of history of BCG immunization. Most tested PID patients had no detectable T-cell immunity to mycobacteria despite history of infection. MSTs may have clinical utility for adoptive immunotherapy in T-cell deficient patients with invasive mycobacterial infections.